A PENGARUH PENDEKATAN KOMUNIKATIF DAN METODE SAM’IYAH SYAFAWIYAH TERHADAP TINGKAT KETERAMPILAN BERBICARA BAHASA ARAB: Indonesia - Oktavia Ratnaningtyas (Muróbbî: Jurnal Ilmu Pendidikan, 2020)
This research was motivated by the weakness of Arabic speaking skills of class VIII students of MTs Miftahur Rosyidin Banjardowo Jombang. So to improve speaking skills I tried to use a communicative approach and the sam'iyah syafawiyah method. Referring to the above background, this paper focuses on the effect of a communicative approach on the level of Arabic speaking skills of class VIII students of MTs Miftahur Rosyidin Banjardowo Jombang, and the effect of the sam'iyah syafawiyah method on the level of Arabic speaking skills of students of class VIII MTs Miftahur Rosyidin Banjardowo Jombang and the effect of the communicative approach and the sam'iyah syafawiyah method on the level of Arabic speaking skills of eighth grade students of MTs Miftahur Rosyidin Banjardowo Jombang. To answer the formulation of the first and second problems, the researcher used a regression formula. The third formulation of the researchers used the multiple regression formula by using a questionnaire and then the calculation using SPSS V.16. This research was conducted by taking a sample of 48 students. This type of research is correlation research with a quantitative approach. The results of the study stated that the results of the partial test regression analysis showed: 1) there was a significant effect in the application of a communicative approach to the Arabic speaking ability of students at Mts Miftahur Rosyidin Banjardowo Jombang which was proven by the presence of T count = 2,245 > T table = 2,012. 2) And there is a significant effect in the Sam'iyah Syafawiyah Method on the Arabic speaking ability of students at Mts Miftahur Rosyidin Banjardowo Jombang which is proven by T count = 2,969 > T table = 2,012. 3) there is a significant influence in the application of the communicative approach and the sam'iyah syafawiyah method on the Arabic speaking ability of students at Mts Miftahur Rosyidin Banjardowo Jombang which is proven by the results of the multiple linear regression equation simultaneous test, with the results of the analysis of the calculated F = 6.709 > F table = 2.83 and the probability value is 0.03 <0.05. Which means, that the application of a communicative approach and the sam'iyah syafawiyah method makes it easier for students to improve students' Arabic speaking skills at Mts Miftahur Rosyidin Banjardowo Jombang